The Politics of Securitization in Democratic Indonesia - Kurniawan, Yandry (Springer International Publishing, 2018)
The book presents a novel analytical perspective on Indonesia's security policies during its transition to democracy. Kunaiwan's analysis revolves around extraordinary measures and normal politics in response to the existential threat to the Indonesian state. This perspective is at the centre of the analysis which examines the process of securitization and desecuritization taken by the Indonesian government. This volume is essential reading for practitioners, students of Indonesian politics and researchers alike.